2008
DOI: 10.1111/j.1751-7133.2008.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria in Nondiabetic and Nonhypertensive Systolic Heart Failure Patients

Abstract: The American Diabetes Association and the National Kidney Foundation define microalbuminuria as an albumin (microg)/creatinine (mg) ratio (ACR) between 30 and 300 microg/mg regardless of sex. Microalbuminuria is associated with increased cardiovascular risk. The authors evaluated the prevalence of microalbuminuria in nondiabetic and nonhypertensive systolic heart failure (SHF) patients. Twenty-seven SHF patients, 18 years and older, with New York Heart Association functional classes II through IV and left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Although physicians have long recognized that dysfunction of either heart or kidney seldom occurs in isolation, only recently has the concept of the cardiorenal syndrome (CRS), along with a classification system, been proposed [1]. Studies have shown close heart-kidney interactions, for example chronic kidney dysfunction (CKD) increases risk for cardiovascular events, and patients with chronic heart failure (CHF) and microalbuminuria or CKD have worse outcomes than those with CHF alone [2-4]. However, the underlying mechanisms remain poorly understood and therapeutic options are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although physicians have long recognized that dysfunction of either heart or kidney seldom occurs in isolation, only recently has the concept of the cardiorenal syndrome (CRS), along with a classification system, been proposed [1]. Studies have shown close heart-kidney interactions, for example chronic kidney dysfunction (CKD) increases risk for cardiovascular events, and patients with chronic heart failure (CHF) and microalbuminuria or CKD have worse outcomes than those with CHF alone [2-4]. However, the underlying mechanisms remain poorly understood and therapeutic options are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of microalbuminuria was found to be significantly higher in CHF patients than in healthy individuals, even in the absence of diabetes mellitus and hypertension, and these patients had worse outcomes compared with CHF patients without microalbuminuria 7, 8 .…”
Section: Introductionmentioning
confidence: 91%
“…Even higher percentages were found in the NHANES cohort from 1999–2004 [38]. In a case control study including non-diabetic and non-hypertensive patients it has been found that elevated ACR was significantly higher in patients with systolic heart failure, if compared to matched controls [39].…”
Section: Discussionmentioning
confidence: 93%